Elotuzumab plus lenalidomide and dexamethasone in relapsed/refractory multiple myeloma: Extended 4‐year follow‐up and analysis of relative progression‐free survival from the randomized ELOQUENT‐2 trial. Issue 20 (11th September 2018) - Dimopoulos, Meletios A.; Lonial, Sagar; Betts, Keith A.; Chen, Clara; Zichlin, Miriam L.; Brun, Alexander; Signorovitch, James E.; Makenbaeva, Dinara; Mekan, Sabeen; Sy, Oumar; Weisel, Katja; Richardson, Paul G.
Abstract : Background: The randomized phase 3 ELOQUENT‐2 study (NCT01239797) evaluated the efficacy and safety of elotuzumab plus lenalidomide and dexamethasone (ELd) versus lenalidomide and dexamethasone (Ld) in relapsed/refractory multiple myeloma (RRMM), and to date, has the longest follow‐up of any monoclonal antibody in patients with RRMM. Methods: In this extended 4‐year follow‐up of the ELOQUENT‐2 trial, the coprimary endpoints of progression‐free survival (PFS) and overall response rate as well as the secondary endpoint of overall survival were assessed. In the absence of head‐to‐head trials comparing Ld‐based triplet regimens to guide treatment selection, 4 randomized controlled trials—ELOQUENT‐2, ASPIRE, TOURMALINE‐MM1, and POLLUX—were indirectly compared to provide insight into the relative efficacy of these regimens in RRMM. Results: Data at 4 years were consistent with 2‐ and 3‐year follow‐up data: ELd reduced the risk of disease progression/death by 29% versus Ld (hazard ratio, 0.71) while maintaining safety. The greatest PFS benefit among the assessed subgroups was observed in patients at the median time or further from diagnosis (≥3.5 years) with 1 prior line of therapy, who had a 44% reduction in the risk of progression/death, and in patients in the high‐risk category, who had a 36% reduction in favor of ELd. This regimen also showed a relative PFS benefit that was maintained beyond 50 months. Conclusions: The sustained PFS benefit and long‐term safety of ELd at 4 years, similar to those observed at 2 and 3 years, support ELd as a valuable therapeutic option for the long‐term treatment of patients with RRMM. Abstract : The sustained efficacy of elotuzumab plus lenalidomide and dexamethasone observed throughout an extended 4‐year follow‐up of the ELOQUENT‐2 trial is further supported by findings from a descriptive analysis of the relative progression‐free survival benefit of this regimen over time. This, combined with a well‐established long‐term safety and tolerability profile, supports elotuzumab plus lenalidomide and dexamethasone as a valuable therapeutic option for the long‐term treatment of relapsed/refractory multiple myeloma.